A Gas‐Sensitive SPIM Sensor for Detection of Ethanol Using SnO2 as Sensing Element (Phys. Status Solidi A 12∕2019). Issue 12 (19th June 2019) - Wang, Mengyun; Truong, Hoang A.; Werner, Carl F.; Miyamoto, Ko‐ichiro; Yoshinobu, Tatsuo
Abstract : Gas Sensors A gas‐sensitive scanning photo‐induced impedance microscopy (SPIM) sensor using tin dioxide (SnO2 ) as sensing element is proposed, which detects the local impedance change on the sensor surface in response to ethanol vapor. Thanks to the light‐addressability of SPIM, images of photocurrent changes are obtained by using a scanning laser beam, which can be applied to the visualization of gas‐concentration distributions on the sensing surface. More details can be found in article number 1800766 by Mengyun Wang, Tatsuo Yoshinobu, and co‐workers.